Pro12Ala polymorphism of the peroxisome proliferator-activated receptor-γ gene in women with polycystic ovary syndrome - Yilmaz, Murat; Ali Ergün, Mehmet; Karakoç, Ayhan; Yurtçu, Erkan; Çakir, Nuri; Arslan, Metin (Gynecological endocrinology, 2006)
Aim. The present study was designed to examine the relationship between Pro12Ala polymorphism of the peroxisome proliferator-activated receptor-γ gene (PPAR-γ) and clinical and hormonal characteristics in women with polycystic ovary syndrome (PCOS). Materials and methods. One hundred patients with PCOS and 100 healthy subjects were included in the study. Serum levels of sex steroids were measured. Insulin resistance was evaluated by homeostasis model assessment (HOMA). The responses of glucose and insulin to an oral glucose tolerance test were analyzed by calculating the respective area under the curve (AUC) by the trapezoidal method. We used the restriction fragment length polymorphism technique and polymerase chain reaction to examine Pro12Ala polymorphism in exon 2 of PPAR-γ. Results. Pro12Ala polymorphism of PPAR-γ was significantly elevated in control subjects (22%) compared with PCOS subjects (15%). All of the Pro12Ala polymorphisms of PPAR-γ were heterozygous. When PCOS subjects with the Pro allele and the Ala allele of PPAR-γ were compared, the latter had lower free testosterone, androstenedione, dehydroepiandrosterone sulfate, insulin and C-peptide levels, as well as lower luteinizing hormone follicle-stimulating hormone ratio, HOMA insulin resistance index, AUCinsulin, Ferriman-Gallwey score, acne, body mass index and waist-to-hip ratio. Conclusion. We suggest that Pro12Ala polymorphism of the PPAR-γ gene may be a modifier of insulin resistance in women with PCOS.